The Relationship between Inflammatory Marker Levels and Hepatitis C Virus Severity - Qitian He; Quan He; Xue Qin; Shan Li; Taijie Li; Li Xie; Yan Deng; Yu He; Yongbin Chen; Zhifu Wei (Gastroenterology Research and Practice)
Background. Red cell distribution width (RDW) and platelet-lymphocyte ratio (PLR) have been studied in a variety of etiological diseases. We aim to investigate the relationship between RDW and PLR and the severity of hepatitis C virus- (HCV-) related liver disease. Methods. We included fifty-two chronic HCV and 42 HCV-related cirrhosis patients and 84 healthy controls. Hematological and virological parameters and liver function biomarkers of HCV-related patients at admission were recorded. Results. RDW, RDW-to-platelet (RPR), and 1/PLR values in HCV-related cirrhosis patients were significantly higher than in chronic HCV patients and healthy controls (all P<0.001). The aspartate aminotransferase (AST)/alanine aminotransferase (ALT) ratio (AAR), AST-to-platelet ratio index (APRI), and fibrosis index based on the four factors (FIB-4) scores in HCV-related cirrhosis patients were significantly higher than in chronic HCV patients (all P<0.001). The areas under the curve of the RDW, RPR, and 1/PLR for predicting cirrhosis were 0.791, 0.960, and 0.713, respectively. Bivariate logistic regression analysis showed that RDW could independently predict the presence of cirrhosis in chronic HCV patients. Conclusions. RDW, RPR, and PLR may be potential markers for estimating HCV severity.